The recurrence of negatively reinforced responding of humans. - Alessandri, Jérôme; Lattal, Kennon A.; Cançado, Carlos R.X. (Journal of the Experimental Analysis of Behavior, 2015)
The recurrence of negatively reinforced responding of humans was studied in three experiments. In each experiment during Baseline, key-pressing produced 3-s timeouts from a requirement to exert finger pressure on a force cell according to variable- or fixed-ratio schedules of reinforcement. In Experiment 1, resurgence was studied by arranging a differential-reinforcement-of-other-behavior schedule in the second phase, and extinction in the Test phase. In Experiment 2, ABA renewal was studied by extinguishing responding in the second phase in a different context and, in the Test phase, by presenting the Baseline-phase context when extinction still was in effect. In Experiment 3, reinstatement was studied by arranging extinction in the second phase, followed by the delivery of response-independent timeouts in the Test phase. Resurgence and renewal occurred consistently for each participant in Experiments 1 and 2, respectively. In Experiment 3, reinstatement was observed less consistently in four participants. The results of these experiments replicate and extend to negatively reinforced responding previous findings of the resurgence and renewal of positively reinforced responding obtained mainly with nonhuman animals.